Personal Investment in L2 Task Design and Learning: A Case Study of Two Japanese Learners of English. - Lambert, Craig; Minn, Danny (Univertsity of Seville, 2007)
The present study explores ways in which personal investment might be operationalized as a condition in L2 task design, how this condition might affect L2 learning, and how the effects of the condition might be effectively measured in future empirical research. Two intermediate-level Japanese females completed three task types (instructional, narrative, opinion) in two conditions (personal investment & teacher investment). The personal investment (PI) condition required them to supply the content and resource materials on which the pedagogic tasks operated, whereas in the teacher investment (TI) condition these materials were supplied as part of the task as set. Three types of data were then triangulated in order to explore ways in which this condition may affect L2 performance and metacognition on tasks: oral performances, post-performance protocols, and questionnaires. Results indicate that performances in the PI condition contained more elaboration and more associations with existing knowledge. The condition may thus provide one means of controlling the ‘need’ component of Laufer and Hulstijn’s (2001) Involvement Load Hypothesis. The study explores the potential of tasks in L2 acquisition, providing both a heuristic and initial hypotheses for future study of relationships between this task condition, L2 performance and metacognition.